Transformasi Digital, Manajemen Pengetahuan, dan Pengaruhnya terhadap Kinerja Karyawan Universitas Swasta Bandung - Rinto Yuniarso; Henky Lisan Suwarno (Value : Jurnal Manajemen dan Akuntansi, 2025)
Digital transformation is now a strategic imperative in higher education human resources, crucial for boosting administrative staff performance. This study investigates how digital transformation impacts employee performance, using knowledge management as a mediating factor. Conducted at a private university in Bandung, the research employed a quantitative method with a sample of 100 administrative employees. Using PLS-SEM analysis, the results show that digital transformation significantly improves both knowledge management and employee performance. Knowledge management also proved to be a strong mediator. These findings confirm that digital tools must be paired with structured knowledge management to sustainably enhance employee outcomes, providing a blueprint for universities to develop integrated digital strategies.